2020
DOI: 10.1186/s12905-020-01031-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vaginal administration of conjugated estrogens tablet on sexual function in postmenopausal women with sexual dysfunction: a double-blind, randomized, placebo-controlled trial

Abstract: Background: Female sexual dysfunction (FSD) is prevalent in women with genitourinary syndrome of menopause (GSM). Vaginal estrogen is effective GSM treatment. This study was primarily aimed to evaluate the effects of vaginal administration of conjugated estrogens tablet on postmenopausal FSD using the Female Sexual Function Index (FSFI). Secondary aims were to evaluate vaginal pH, Vaginal Maturation Value (VMV), Normal Flora Index (NFI) and Most Bothersome Symptoms (MBS) changes. Methods: A double-blind trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…90 In healthy postmenopausal women with sexual dysfunction, a conjugated estrogen tablet improved vaginal pH and vaginal maturation values but not sexual function. 91 It should be noted that in women with breast cancer estrogens are contraindicated. With inconclusive findings across different studies, further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…90 In healthy postmenopausal women with sexual dysfunction, a conjugated estrogen tablet improved vaginal pH and vaginal maturation values but not sexual function. 91 It should be noted that in women with breast cancer estrogens are contraindicated. With inconclusive findings across different studies, further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…This result, however, is limited because of the small number of participants included in the analysis (Supplemental Digital Content, Appendix B, http://links.lww.com/MENO/B126). 32 Low Low Some concerns Low Some concerns Some concerns Caruso et al 34 Some concerns Some concerns High Some concerns Some concerns High Cruz et al 36 Low Low High Low Some concerns High Ferrante et al 38 Low Low High High Some concerns High Hirschberg et al 39 Low Low High Low Some concerns High Lillemon et al 41 Some concerns Some concerns Some concerns Low Some concerns High Mac Bride 42 Some concerns Low Some concerns Low High High MsFLASH VHT Diem et al, 45 Mitchell et al, 46 Jensen, 47…”
Section: Estrogen Plus Progestogen Therapy Versus Controlmentioning
confidence: 99%
“…The study showed no significant changes in the Female Sexual Function Index. However, a significant improvement in the vaginal pH and Vaginal Maturation Value was observed [ 21 ].…”
Section: Menopause Hormone Therapy In Current Practicementioning
confidence: 99%
“…Thus, there are several therapeutic schemes to improve genitourinary symptoms. Current treatment is based on topical estrogen alone [ 21 , 22 , 23 , 24 , 25 , 26 ] or combined with testosterone [ 27 , 28 ] which has shown improvements over time in the fields of vaginal trophicity, arousal, orgasm, and satisfaction ( Table 1 ). For moderate/severe dyspareunia the treatment uses daily intravaginal 0.50% DHEA ovules (suppositories—Prasterone) for 12 weeks [ 29 , 30 ].…”
Section: Menopause Hormone Therapy In Current Practicementioning
confidence: 99%